Patterns of Social Embeddedness in Later Adulthood: Gender and Other Covariates - Sarmitė Mikulionienė; Inga Gaižauskaitė; Vaidas Morkevičius (Gender a Výzkum)
The concept of social exclusion is widely used in academia and social policy discourse in European countries. However, one of the constituents of social exclusion, namely, exclusion from social relationships, remains unclear and underdeveloped both conceptually and empirically. Moreover, knowledge on the patterns of exclusion from social relationships among men and women in later adulthood is even less advanced. Therefore, we developed a multidimensional scale for measuring an individual's level of embeddedness in social relationships and examined the gender patterns of social embeddedness. We applied latent class analysis to survey data collected on a sample of 2015 residents of Lithuania, Latvia, and Estonia aged 50+. We derived a seven-class model based on a continuum from strong to weak social embeddedness. We identified two classes with a high level of exclusion from social relations and, conversely, two classes with a high level of social embeddedness. Subsequent multinomial regression analysis revealed that gender was a statistically significant predictor in the cases of the most excluded class and one of the most socially embedded classes.